Household economic empowerment model: Case study of Aisyiyah Eknaker assembly Medan city - Br. Purba, Devia Syahfitri; Hasibuan, Reni Ria Armayani; Nasution, Juliana (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
This research analyzes the household economic empowerment model developed by the Economic and Employment Council (EKNAKER) of Aisyiyah Medan City through programs such as Bina Usaha Ekonomi Keluarga Aisyiyah (BUEKA), MSME Bazaar, Aisyiyah Entrepreneurial School (SWA), and Aisyiyah Cooperative. Using a qualitative methodology, data were collected through interviews, observations, and documentation, and data were analyzed using NVivo 15. Findings indicate that EKNAKER enhances homemakers' economic capacity through training, capital support, and marketing initiatives. Key challenges include limited capital and low digital literacy; however, community support and an effective organizational structure are vital for the program's success. Public interest statements This study examines EKNAKER Aisyiyah Medan’s household economic empowerment through BUEKA and MSME Bazaars. Despite limited capital and low digital literacy, strong community support boosts homemakers’ economic capacity, improves welfare, and strengthens family resilience, offering a replicable model for broader community development